Flexural behavior and cracking of lightweight RC beams containing coarse and fine slag aggregates. (January 2023) - Ismail, Mohamed K.; Hassan, Assem A.A.; AbdelAleem, Basem H.; El-Dakhakhni, Wael
Abstract: This study contributes to investigating the potential of using lightweight slag aggregates (SL) in structural applications, as well as exploring the near-optimal options of using fine and/or coarse SL to construct high-performance lightweight structural elements. Large-scale self-consolidating reinforced concrete beams were cast with different combinations of lightweight SL and conventional aggregates. All beams were tested under four-point flexural loading, and their performance was evaluated in terms of cracking behavior, failure mode, load–deflection response, cracking and ultimate moments, ductility, and energy absorption capacity. The experimental cracking and ultimate moments of all tested beams were compared to those obtained theoretically by existing widely used design standards. The results indicated that lightweight SL can be used to develop successful self-consolidating concrete with a minimum density of 1856 kg/m 3 and compressive strength of 35 MPa. Beams cast with either lightweight fine or coarse SL showed adequate structural capacity, in addition to satisfying standardized serviceability limit states of cracking and deflections. Lightweight coarse SL appeared to have a better potential for producing lighter composite with superior structural capabilities compared to lightweight fine SL. The results also showed that existing design standards conservatively estimated the ultimate capacity of beams made with SL with a safety margin in the range of 1.04 ∼ 1.36.